Avaliação e textualidade – contributos para a elaboração de dispositivos de construção e análise de instrumentos de avaliação - Amor, Emília (Revista da Associação Portuguesa de Linguística, 2019)
With this text, we intend to characterize a set of highly standardized pedagogical evaluation tools – conventional tests and examination papers – as textual objects. Hence, we will focus on some textualization mechanisms, which support their global functioning, as well as on the specifics of contextual use of the same objects. Additionally, we propose plans, concepts and rules which, in a systematic way, can integrate a twofold model, able to accommodate different moments and aims: a) production of the said evaluation instruments; b) their analysis which can be related to the obtained results.